Ultra-low-dose oral contraceptive pill: a new approach to a conventional requirement - Ahuja, Meenakshi; Pujari, Pramod (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Combined oral contraceptives (COCs) offer a convenient, safe, effective, and reversible method of contraception. However, their use is limited by side effects. Several strategies have been suggested to make COC use more acceptable among women. Reduction in the dose of estrogen is a commonly accepted approach to reduce the side effects of COC. Use of newer generation of progestins, such as gestodene, reduces the androgenic side effects generally associated with progestogens. Furthermore, reduction in hormone-free interval, as a 24/4 regimen, can reduce the risk of escape ovulation (hence preventing contraceptive failure) and breakthrough bleeding. It also reduces hormonal fluctuations, thereby reducing the withdrawal symptoms. A COC with gestodene 60 µg and ethinylestradiol (EE) 15 µg offers the lowest hormonal dose in 24/4 treatment regimen. This regimen has been shown to offer good contraceptive efficacy and cycle control. With the progress of treatment cycles, the incidence of breakthrough bleeding reduces. Gestodene/EE low dose 24/4 regimen was associated with lower incidence of estrogen-related adverse events, such as headache, breast tenderness, and nausea. Furthermore, COCs containing low dose of estrogen have not been associated with any adverse effect on haemostasis in healthy women. Ultra-low-dose COCs can be considered in women who are at risk of developing estrogen-related side effects.